An integrated planning tool for design of recycled water distribution networks. (October 2016) - Lee, Eun Jung; Freyberg, David L.; Criddle, Craig S.
Abstract: Pipeline design of urban recycled water networks involves thousands of decisions to ensure delivery of water to multiple use locations with pipelines and pump stations correctly located, optimally sized, and compatible with existing infrastructure. Here, we introduce PRODOT, P ipelineRO uting andD esignO ptimizationT ool, software that identifies near-minimum-cost pipeline routes; accounts for existing configurations, legal, environmental or safety concerns, and trade-offs in pipeline length, pipe installation methods, traffic congestion during construction; optimizes pump station locations, pumping energy, pipe diameters and pressure classes; and includes theoretical additional capacity of each pipe, facilitating future expansion. We illustrate the utility of PRODOT with a case study for a local utility comparing PRODOT-generated configurations to a configuration proposed by an experienced consulting firm. The comparison shows that PRODOT produces pipeline configurations similar to the consulting firm's proposal with improvements by effectively and more broadly incorporating options the consultant may not have considered. Highlights: Near-minimum-cost pipeline configurations for recycled water distribution systems. Οptimal pipe routing, diameters, pressure classes, pump locations, and energy demand. Inclusion of many pragmatic constraints typical of complex urban environments. Inclusion of theoretical additional capacity of each pipe for future expansion. Consistency with and improvement on the design of an experienced consulting firm.